Oncological outcomes of obstructed locally advanced rectal cancer in the era of multi-modal therapy - Franklyn, Joshua; Varghese, Gigi; Rghunath, Rajat; Sebastian, Tunny; Jesudason, Mark Ranjan (International Surgery Journal, 2018)
Background: The management of locally advanced rectal cancer is multi-modal. In India, a number of patients present with features of intestinal obstruction and are diverted prior to initiation of chemo-radiation therapy. The purpose of this paper is to study the demographics and oncological outcomes of obstructed locally advanced rectal cancer (OLARC) requiring pre-therapy diversion colostomy in comparison with patients who did not need pre-treatment diversion (non-obstructed group). Methods: This is a retrospective analysis of a prospective data-base. Patients diagnosed with non-metastatic locally advanced adenocarcinoma of the rectum in a colorectal unit of a tertiary care teaching hospital between August 2012 and December 2014 were analyzed. Data was collected from hospital records and telephonic interviews. Results: Two hundred and thirteen patients were diagnosed to have locally advanced rectal cancer. One hundred and fifty patients (70.4%) did not have features of intestinal obstruction and received NACRT upfront and 63 (29.6%) required pre-therapy diversion colostomy. Thirty-nine patients (61.9%) completed therapy (neo-adjuvant chemo-radiotherapy followed by Surgery and adjuvant chemotherapy) in the obstructed group, compared to 127(84.7%) in the non-obstructed group (0<0.05) who completed all components of cancer directed therapy. The 3-year overall survival (OS) of the obstructed and non-obstructed groups was 59% vs 90% (p<.001) and the disease-free survival (DFS) was 51% and 76% (p<0.01) respectively. Conclusions: In the era of multi-modal therapy, patients with obstructed locally advanced rectal cancer have worse oncological outcomes with respect to overall and disease-free survival.